Epidemiology, impact and control of bovine cysticercosis in Europe: a systematic review. Issue 1 (December 2016) - Laranjo-González, Minerva; Devleesschauwer, Brecht; Gabriël, Sarah; Dorny, Pierre; Allepuz, Alberto
Abstract Background Bovine cysticercosis in Europe has been known for centuries but the data showing the occurrence of this zoonosis are scarce. The aim of this paper is to review and present the current knowledge on bovine cysticercosis in Europe. Methods We conducted a systematic review of studies published between 1990 and November 2014. Qualitative and quantitative data on prevalence, risk factors, burden and interventions were extracted and analysed. Results Reports on prevalence were available for 23 European countries, mostly from western and central Europe; for a few of these only data before 1990 were available. Prevalence based on meat inspection was generally low (below 6.2 % in 95 % of the records) and varied between and within countries. Serology and detailed meat inspection provided a higher prevalence range (0.41–14 %). Only few studies analysing risk factors were identified. Reported factors related to access to pastures and risky waters, dairy production and uncontrolled human defecation in the proximity of the farm among others. Only one estimate of the economic impact of the disease could be identified. Recommended interventions were focused on increasing diagnostic tests sensitivity or the application of risk based surveillance strategies. Conclusions There is a lack of complete and updated data on most countries, especially in eastern Europe. Further risk factor studies might be needed together with estimates on the burden of the disease in all European countries. Risk-based interventions are being encouraged but current data are limited to guide this approach.